2022
DOI: 10.1039/d2ce00754a
|View full text |Cite
|
Sign up to set email alerts
|

Near-room-temperature dielectric switch and thermal expansion anomaly in a new hybrid crystal: (Me2NH2)[CsFe(CN)5(NO)]

Abstract: A new hybrid crystal, (Me2NH2)[CsFe(CN)5(NO)], featuring a double-layered nitroprusside-based inorganic framework with cubic-like cages encapsulating organic cations, undergoes a near-room-temperature phase transition accompanying with dielectric switch and thermal expansion anomaly....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Recently, [(CH 3 ) 2 NH 2 ][CsFe(CN) 5 (NO)] was reported to display dielectric switching, but no photoresponse was reported. [14] Finally, T-induced dielectric switching and NO photoswitching were reported for (CH 3 NH 3 )[NaFe(CN) 5 -(NO)].H 2 O. [15] These studies show the promise of (A)[MFe-(CN) 5 (NO)].xH 2 O materials, but with some key outstanding questions.…”
Section: Introductionmentioning
confidence: 93%
“…Recently, [(CH 3 ) 2 NH 2 ][CsFe(CN) 5 (NO)] was reported to display dielectric switching, but no photoresponse was reported. [14] Finally, T-induced dielectric switching and NO photoswitching were reported for (CH 3 NH 3 )[NaFe(CN) 5 -(NO)].H 2 O. [15] These studies show the promise of (A)[MFe-(CN) 5 (NO)].xH 2 O materials, but with some key outstanding questions.…”
Section: Introductionmentioning
confidence: 93%
“…Recently, several reports have demonstrated that the co-assembly of various organic cations with the nitroprusside anion [Fe­(CN) 5 (NO)] 2– produces a new class of organic–inorganic hybrid materials with diverse structures and fascinating physical properties. For instance, Yao et al reported a Pbcm to Cmcm phase transition at 207 K in (MA) 2 [Fe­(CN) 5 (NO)] (MA = methylammonium) . However, the antiparallel arrangement of polar MA cations and their dynamical disordering cancel out the total unit cell dipole moment, preventing the emergence of long-range order and electric polarization (Figure , left).…”
Section: Introductionmentioning
confidence: 99%
“…This has allowed phase transition materials to have considerable utility in the areas of switchable devices, information storage, and actuators. Among them, organic–inorganic hybrid perovskite materials are unique phase transition materials that are connected by inorganic frameworks and organic cations through a certain interaction force, integrating the advantages of inorganic phase transition materials and organic phase transition materials. Inorganic metal frameworks show outstanding advantages in optical, semiconducting, and electrical properties. Organic cations have a flexible structure that can be easily modified and are susceptible to movement by temperature, which leads to phase transitions in the material. The combination of these two makes organic–inorganic hybrid perovskite materials stand out among many phase transition materials by their environmental friendliness and structural tunability. Exploiting these advantages, many functionally diverse hybrid organic–inorganic perovskite ferroelectrics have been investigated . Likewise, this unique structure of organic–inorganic hybrid perovskite materials also makes them show their brilliance in optoelectronic field. , …”
Section: Introductionmentioning
confidence: 99%